Building the repertoire of measures of walking in Rett syndrome - Stahlhut, M.; Downs, Jennepher; Leonard, H.; Bisgaard, A.; Nordmark, E. (Informa Healthcare, 2017)
Background: The repertoire of measures of walking in Rett syndrome is limited. This study aimed to determine measurement properties of a modified two-minute walk test (2MWT) and a modified Rett syndrome-specific functional mobility scale (FMS-RS) in Rett syndrome. Methods: Forty-two girls and women with Rett syndrome (median 18.4 years, range 2.4–60.9 years) were assessed for clinical severity, gross motor skills, and mobility. To measure walking capacity, 27 of this group completed a 2MWT twice on two different assessment days. To assess walking performance, the FMS-RS was administered to the total sample of parents (n=42) on two occasions approximately one week apart. Results: There were negative correlations between clinical severity and 2MWT (r= -0.48) and FMS-RS (r= -0.60–0.66). There were positive correlations between gross motor skills and mobility and 2MWT (r=0.51, 0.43) and FMS-RS (r=0.71–0.93, 0.74–0.94), respectively. Test–retest reliability for the 2MWT was good with high intraday and interday correlations (ICC=0.86–0.98). For the 2MWT, the standard error of measurement was 13.8 m and we would be 95% confident that changes greater than 38 m would be greater than within subject error. There was good test–retest reliability for all three distances on the FMSRS (ICC=0.94–0.99). Conclusions: Walking capacity as measured by the 2MWT showed expected but limited relationships with measures of different constructs, providing some support for concurrent validity. Walking performance as measured with the FMS-RS was more strongly consistent with other clinical measures supporting its concurrent validity. Test–retest reliability was good for both the FMS-RS and the 2MWT. Therefore, these measures have the potential to be used in clinical practice and research.